Fairy tail. Master's edition 2 - Mashima, Hiro, 1977- (Kodansha Comics, 2016)
"Natsu and Gray face off against demons from Gray's past and a wizard who can control the future! Meanwhile, Fairy Tail's rival guild, Phantom Lord, has done the unforgivable - smashing the guild hall to the ground! Fairy Tail has never been one for proportional responses, so it's time for an all-out guild war. But Phantom Lord has a secret weapon nobody expected - a powerful dragon slayer of their own! An action-packed 950+ pages of manga from a shonen classic, in a large size at a small price (for guild masters only)."--Back of book